Pemanfaatan Twitter Sebagai Media Promosi Terhadap UMKM - Besti Tiurmaida Pardede; Ririsma Sihombing; Sherly Prissillia Devi; Chandra Bayu Hidayat (Universitas Veteran Bangun Nusantara, 2022)
This study examines how the influence of the use of social media Twitter in promoting small businesses (MSMEs). This research uses a literature study by reviewing previous research. This study uses a qualitative method with data processing using a literature review. The results obtained from this study indicate that the use of social media twitter has a fairly high and positive influence in promoting the MSME business, with the easy twitter feature and tapa budget being the choice of MSME businessme.